A Randomized Controlled Trial Comparing the Efficacy of Cyp3a5 Genotype‐Based With Body‐Weight‐Based Tacrolimus Dosing After Living Donor Kidney Transplantation. Issue 7 (26th February 2016) - Shuker, N.; Bouamar, R.; van Schaik, R. H. N.; Clahsen‐van Groningen, M. C.; Damman, J.; Baan, C. C.; van de Wetering, J.; Rowshani, A. T.; Weimar, W.; van Gelder, T.; Hesselink, D. A.
Abstract : Patients expressing the cytochrome P450 (CYP) 3A5 gene require a higher tacrolimus dose to achieve therapeutic exposure compared with nonexpressers. This randomized‐controlled study investigated whether adaptation of the tacrolimus starting dose according to CYP3A5 genotype increases the proportion of kidney transplant recipients being within the target tacrolimus predose concentration range (10–15 ng/mL) at first steady‐state. Two hundred forty living‐donor, renal transplant recipients were assigned to either receive a standard, body‐weight‐based or a CYP3A5 genotype‐based tacrolimus starting dose. At day 3, no difference in the proportion of patients having a tacrolimus exposure within the target range was observed between the standard‐dose and genotype‐based groups: 37.4% versus 35.6%, respectively; p = 0.79. The proportion of patients with a subtherapeutic (i.e. <10 ng/mL) or a supratherapeutic (i.e. >15 ng/mL) Tac predose concentration in the two groups was also not significantly different. The incidence of acute rejection was comparable between both groups (p = 0.82). Pharmacogenetic adaptation of the tacrolimus starting dose does not increase the number of patients having therapeutic tacrolimus exposure early after transplantation and does not lead to improved clinical outcome in a low immunological risk population. Abstract : This randomized trial shows that in living donor kidney transplant recipients, a tacrolimus starting dose based on the CYP3A5 genotype does not increase the proportion of patients reaching the tacrolimus target concentration range at day 3 posttransplant.